Analysis And Recognition Of Pain In 2d Face Images Of Full Term And Healthy Newborns - Teruel, Gilberto F.; Heiderich, Tatiany M.; Guinsburg, Ruth; Thomaz, Carlos E. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2018.4419, 2018)
This paper proposes a sequence of computational procedures for detecting, interpreting and classifying patterns in frontal two-dimensional images of faces for automatic recognition of pain in newborns. Using data transformation and extraction of statistical characteristics from a real-life, healthy-term newborn image database, it was possible to interpret and model the subjectivity of trained health professionals, quantifying human knowledge in the task of recognizing pain enabling automatic identification. These results were compared with NFCS based classifications by the same professionals of the same images.